2016
DOI: 10.1370/afm.1950
|View full text |Cite
|
Sign up to set email alerts
|

A High Sense of Coherence as Protection Against Adverse Health Outcomes in Patients Aged 80 Years and Older

Abstract: PURPOSEWe set out to assess whether a high sense of coherence (SOC) protects from adverse health outcomes in patients aged 80 years and older who have multiple chronic diseases.METHODS A population-based prospective cohort study in 29 primary care practices throughout Belgium included 567 individuals aged 80 years and older. We plotted the highest tertile of SOC scores in Kaplan-Meier curves representing 3-year mortality and time to first hospitalization. Using Cox proportional hazard regression analyses and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 50 publications
2
40
0
6
Order By: Relevance
“…Sense of coherence is a core component in the salutogenic model of Aaron Antonovsky [75] and is defined as "a global orientation that expresses the extent to which one has a pervasive, enduring though dynamic feeling of confidence that (1) the stimuli deriving from one's internal and external environments in the course of living are structured, predictable, and explicable; (2) the resources are available to one to meet the demands posed by these stimuli; and (3) these demands are challenges, worthy of investment and engagement' [76]. Our findings are consistent with studies that argue that a high sense of coherence allows to better cope with stressors and represents a health promoting factor [71] associated with reduced mortality, increased well-being, and reduced incidence of depression [77,78,79].…”
Section: Endpoints Analysissupporting
confidence: 85%
“…Sense of coherence is a core component in the salutogenic model of Aaron Antonovsky [75] and is defined as "a global orientation that expresses the extent to which one has a pervasive, enduring though dynamic feeling of confidence that (1) the stimuli deriving from one's internal and external environments in the course of living are structured, predictable, and explicable; (2) the resources are available to one to meet the demands posed by these stimuli; and (3) these demands are challenges, worthy of investment and engagement' [76]. Our findings are consistent with studies that argue that a high sense of coherence allows to better cope with stressors and represents a health promoting factor [71] associated with reduced mortality, increased well-being, and reduced incidence of depression [77,78,79].…”
Section: Endpoints Analysissupporting
confidence: 85%
“…Our findings are in accordance with studies reporting that high SOC is associated with positive levels of health in adult life (Elyasi et al, ; Sipilä, Ylöstalo, Joukamaa, & Knuuttila, ). In addition, a systematic review that investigated the association between SOC and oral health behaviors showed that stronger SOC was associated with favorable oral health behaviors (Boeckxstaens et al, ; Elyasi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The positive influence of SOC on OHRQoL and QoL, found in our study, is corroborated by previous investigations, which revealed that high SOC provides adaptive health behavior and ability for resilience (Miettinen et al, ). On a similar note, a holistic view of TMD is of importance, as high SOC contributes to the improvement of the capacity to cope with life stressors and health maintenance, and consequently QoL (Boeckxstaens et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…7 The positive impact of a higher SOC extends into the ninth decade of life and beyond, with people who have scores in the highest tertile having a decreased risk of mortality and functional decline. 8 A way to operationalise the concept of salutogenesis is Health assets. Health assets are factors that predict health and recovery over and above conventional risk factors and are also desirable in their own right.…”
Section: Introductionmentioning
confidence: 99%